The effect of special exercises to develop some of the physical abilities of bodybuilders (Journal of the College of Basic Education, 2022)
The sport of body building is one of the individual games that are characterized by strength, art and will, and it is one of the events that witnessed a great development in the field of training and it is old with its existence. It depends on the output results from muscle work, which is represented by bringing the muscles of the human body to a state of perfection and growth in an aesthetic way through the organized exercise of each muscle of the body, and the special exercises are one of the sports training methods that aim to raise the players’ efficiency in physical terms